Determination of Pb and Mg accumulation in some of the landscape plants in shrub forms - Sevik, Hakan; Cetin, Mehmet; Ucun Ozel, Handan; Ozel, Halil Baris; Mossi, Mansour Mossi Mohammed; Zeren Cetin, Ilknur (Springer Science and Business Media LLC, 2019)
Heavy metals have a separate precaution in the air pollution components as they are not easily deteriorated in nature, they tend to bioaccumulate, they are carcinogenic or poisonous, and they can be toxic even at low concentrations. Therefore, monitoring of heavy metal pollution is of great importance. Plants are frequently used as biomonitors to monitor the heavy metal pollution. However, the heavy metal accumulation capacities of plants can vary considerably depending on the plant species, as well as on the organelle basis and the amount of particulate matter in the environment. It is also very important to determine how much of the heavy metal concentrations found in plants are derived from the plant species and how much from the particulate matter on the organ. In this study, it was aimed to determine the change of heavy metal accumulation in some landscape plants grown in the city center of Kastamonu depending on plant type, plant organism, washing status, and traffic density. For this purpose, leaf and branch samples were collected from individuals of Ligustrum vulgare L., Euonymus japonica Thunb., Biota orientalis L., Juniperus sabina L., Berberis thunbergii DC, Mahonia aquifolium (Pursh) Nutt., and Buxus sempervirens L., which are frequently used in urban landscape designs growing in areas with heavy, low dense, and no traffic. Some of the collected samples were washed, and heavy metal analyses were conducted to determine the amount of Pb and Mg concentrations. It was remarkable that Pb concentration was higher in branches than in the leaves for all the species. And the alteration depending on traffic density on the base of the factors studied was in different proportion depending on the metals.
Keywords: Health, Toxicology and Mutagenesis; Urbanization; Plant; Mercury; Plants; Pollution; Plant Leaves; Heavy Metal; Shrub; Lead; Air Pollution; Metals, Heavy; Landscape; Particulate Matter; Environmental Pollution; Environmental Monitoring; 15. Life on land; 6. Clean water; 12. Responsible consumption; 13. Climate action; 11. Sustainability